How did we get here? Insights into mechanisms of immunity-related GTPase targeting to intracellular pathogens. (October 2022) - Dockterman, Jacob; Coers, Jörn
Abstract : The cytokine gamma-interferon activates cell-autonomous immunity against intracellular bacterial and protozoan pathogens by inducing a slew of antimicrobial proteins, some of which hinge upon immunity-related GTPases (IRGs) for their function. Three regulatory IRG clade M (Irgm) proteins chaperone about approximately 20 effector IRGs (GKS IRGs) to localize to pathogen-containing vacuoles (PVs) within mouse cells, initiating a cascade that results in PV elimination and killing of PV-resident pathogens. However, the mechanisms that allow IRGs to identify and traffic specifically to 'non-self' PVs have remained elusive. Integrating recent findings demonstrating direct interactions between GKS IRGs and lipids with previous work, we propose that three attributes mark PVs as GKS IRG targets: the absence of membrane-bound Irgm proteins, Atg8 lipidation, and the presence of specific lipid species. Combinatorial recognition of these three distinct signals may have evolved as a mechanism to ensure safe delivery of potent host antimicrobial effectors exclusively to PVs. Highlights: Immunity-related GTPases (IRGs) specifically localize to and destroy pathogen-containing vacuoles (PVs). IRGs must differentiate PV membranes from host membranes. We present a three-signal model for IRG recruitment to PVs. Lipidated Atg8 and the absence of host IRG-clade M are two signals for IRG recruitment. IRGs may specifically bind lipid species enriched on PVs, comprising a third signal.